Densely Packed and Highly Ordered Carbon Flower Particles for High Volumetric Performance. Issue 7 (20th July 2021) - Gong, Huaxin; Chen, Shucheng; Ning, Rui; Chang, Ting-Hsiang; Tok, Jeffrey B.-H.; Bao, Zhenan
Abstract : Densely Packed Carbon Flower Particles A strategy to synthesize high‐bulk‐density carbon materials by self‐assembling carbon flower particles into ordered arrays is reported in article number 2000067 by Zhenan Bao and co‐workers. The developed materials show a large increase in bulk density, and they are promising for many energy storage‐related applications.